Analysis of Factors Affecting Manufacturing Companies in Indonesia Performing a Switching Auditor - Winata, Atika Sukma; Anisykurlillah, Indah (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This study aims at analyzing the influence of the Public Accountant Firms Size, Size of Company, Financial Distress, Audit Opinion and Management Turnover toward Auditor Switching. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange during the period 2011-2015 consisting of 134 companies. The sample was obtained by purposive sampling technique which resulted in the sample of 26 companies. Methods of data analysis using logistic regression and SPSS 21 using data and other information obtained from Annual Report. Results of this study shows that the Public Accountant Firms Size and Management Turnover have significant impact toward auditor switching, size of company have influence auditor switching. Financial distress and audit opinion did not effect auditor switching significantly. The value of Nagelkerke R Square is 0.283. conclusions of this study is the Public Accountant Firms Size and Management Turnover have significant impact toward auditor switching, size of company have influence auditor switching. Financial distress and audit opinion did not effect auditor switching significantly.